2018
DOI: 10.1111/jopr.12795
|View full text |Cite
|
Sign up to set email alerts
|

A Validation Study of the Impression Replica Technique

Abstract: The impression replica technique overestimates gaps within the range of 2% to 11%. The validation of the replica technique enables the method to be used as a reference when testing other methods for evaluating fit in dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Evaluating the marginal fit of crowns can be challenging. Although the replica technique has been validated for the evaluation of the marginal and internal fit of crowns [ 23–25 ], it does have some shortcomings and can be technique-sensitive. One of the shortcomings of this technique is a limited number of measurement points for each restoration, therefore it may not represent the true circumferential fit of a crown; however, as the technique has been used extensively in prosthodontics, it makes comparisons to other studies easier.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the marginal fit of crowns can be challenging. Although the replica technique has been validated for the evaluation of the marginal and internal fit of crowns [ 23–25 ], it does have some shortcomings and can be technique-sensitive. One of the shortcomings of this technique is a limited number of measurement points for each restoration, therefore it may not represent the true circumferential fit of a crown; however, as the technique has been used extensively in prosthodontics, it makes comparisons to other studies easier.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the assessment of in vivo wear has been conducted using laser scanner technology or profilometry with tooth replicates either in acrylic resin or stone (Heintze, Cavalleri, Forjanic, Zellweger, & Rousson, 2006;Mehl, Gloger, Kunzelmann, & Hickel, 1997;Pintado, Anderson, DeLong, & Douglas, 1997;Rodriguez & Bartlett, 2010;Rodriguez, Curtis, & Bartlett, 2009;Schlueter, Ganss, Sanctis, & Klimek, 2005). While this has proven to be effective, there are some errors involved in the replication process with the impression and the replicating materials (Hsu et al, 2019;Rodriguez & Bartlett, 2010;Segerström, Wiking-Lima de Faria, Braian, Ameri, & Ahlgren, 2018). Also, the resolution accuracy of the laser scanners varies from 5 to 20 μm and can affect the quantification of wear.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the impression replica technique using only slices of the 2 D fit may be as accurate as the triple-scan protocol for internal fit measurements. Other studies have evaluated the impression replica technique for validity and reliability and have concluded that it has a tendency to overestimate the gap with 2 to 11% and have moderate variations in reliability [5,6]. For cervical area gap and internal gap, the impression replica technique had slightly higher values but these differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 94%